Effect of free oxygen radical anions and free electrons in a Ca12Al14O33 cement structure on its optical, electronic and antibacterial properties - Chaiwat Phrompet; Chaval Sriwong; Pornjuk Srepusharawoot; Santi Maensiri; Prinya Chindaprasirt; Chesta Ruttanapun (My University, 2019)
The aim of this work was to investigate the effect of free oxygen radicals and free electrons in a Ca12Al14O33 (C12A7) cement structure on the optical, electronic and antibacterial activity of this material. Ca12Al14O33 was successfully fabricated via rapid heating to high temperatures by high frequency electromagnetic induction. Ca12Al14O33 cement samples were characterized using XRD and UV-Vis-DRS spectroscopy. The morphology and chemical composition of the samples were also investigated using SEM and EDS techniques. The presence of free oxygen radicals (O2-ions) in the insulating structure of Ca12Al14O33 was confirmed using Raman spectroscopy showing a spectrum peak at 1067 cm-1. The excitation of free electrons in the Ca12Al14O33 cement was indicated by UV-Vis absorption spectra at 2.8 eV and an optical energy gap of 3.5 eV, which is consistent with the first-principles calculations for the band energy level. The effects of free oxygen radicals and free electrons in the Ca12Al14O33 structure as antibacterial agents against Escherichia Coli (E. coli) and Staphylococcus Aureus (S. aureus) were investigated using an agar disk-diffusion method. The presence of O2- anions as a reactive oxygen species (ROS) at the surface of Ca12Al14O33 caused inhibition of E. coli and S. aureus cells. The free electrons in the conducting C12A7 reacted with O2 gas to produce ROS, specifically super oxides (O2-), superoxide radicals (O2•-), hydroxyl radicals (OH•) and hydrogen peroxide (H2O2), which exhibited antibacterial properties. Both mechanisms were active against bacteria without effects from nano-particle sized materials and photocatalytic activity. The experimental results showed that the production of ROS from free electrons was greater than that of the free O2- anions in the structure of Ca12Al14O33. The antibacterial actions for insulating and conducting Ca12Al14O33 were different for E. coli and S. aureus. Thus, Ca12Al14O33 cement has antibacterial properties that do not require the presence of nano-particle sizes materials or photocatalysis.
Keywords: Catalytic Processes in Materials Science